Long‐term efficacy and safety of infliximab maintenance therapy in patients with plaque‐type psoriasis in real‐world practice. (13th August 2014) - Shear, N.H.; Hartmann, M.; Toledo‐Bahena, M.; Katsambas, A.; Connors, L.; Chang, Q.; Yao, R.; Nograles, K.; Popmihajlov, Z.; ,
Summary: Background: Tumour necrosis factor‐α inhibitors, including infliximab (IFX), can improve disease control of plaque‐type psoriasis. Objectives: The Real‐World Assessment of Long‐Term Infliximab Therapy for Psoriasis (REALITY) study evaluated the efficacy and safety of maintenance IFX therapy in typical clinical settings. Methods: In this prospective, observational, open‐label, multicentre study in patients with plaque‐type psoriasis, IFX 5 mg kg was infused at weeks 0, 2 and 6, and every 8 weeks thereafter during a 50‐week treatment phase. The primary outcome was ≥ 75% Psoriasis Area and Severity Index (PASI) improvement from baseline to week 50. Patients with ≥ 25% PASI improvement from baseline to the end of the treatment phase were potentially eligible to enter a 48‐week extended treatment phase. Response maintenance and other efficacy measures were evaluated. Adverse events (AEs) were collected. Results: In total 660 patients enrolled. Of 521 efficacy‐evaluable treatment phase patients (66% male, mean age 46·5 years, mean PASI 18·1), 56·8% achieved PASI 75 at the end of the treatment phase. Response was maintained at week 50 by 64·7% (205/317) of patients who achieved PASI 75 at week 14. During extended treatment, 66·3% (112/169) of patients attained PASI 75 at week 98; response was maintained at week 98 by 71·6% (101/141) of those who achieved PASI 75 at week 50. IFX was generally well tolerated. During treatment, 7·6% (50/659) of patients had serious AEs. During extended treatment, 4·1% (eight of 193) of patients had serious AEs. Conclusions: PASI 75 response was achieved by 56·8% and 66·3% of patients at weeks 50 and 98, respectively. The AE pattern was consistent with previous reports. Abstract : What's already known about this topic? Tumour necrosis factor‐α inhibitors have been shown to improve moderate‐to‐severe plaque psoriasis in controlled clinical trials. What does this study add? The long‐term safety and efficacy of infliximab in patients with plaque‐type psoriasis in real‐world practice were evaluated. At the end of the treatment phase, 56·8% of patients achieved 75% Psoriasis Area and Severity Index improvement (PASI 75) at week 50. Among patients who received treatment in year two of the study, 66·3% achieved PASI 75 at week 98. Safety results were consistent with previous reports of long‐term biological treatment.